Shared medical appointments in English primary care for long-term conditions: a qualitative study of the views and experiences of patients, primary care staff and other stakeholders - Graham, Fiona; Martin, Helen; Lecouturier, Jan; O’Donnell, Amy; Tang, Mei Yee; Jackson, Katherine; Sniehotta, Falko F.; Kaner, Eileen (BMC primary care, 2022)
Shared medical appointments (SMAs) or group consultations have been promoted in primary care to improve workload pressures, resource-use efficiency and patient self-management of long-term conditions (LTCs). However, few studies have explored stakeholders’ perspectives of this novel care delivery model in the English NHS context, particularly patients’ views and experiences of SMAs.
Gesehen am 29.11.2022